CRÉATION DE SUPPORTS INTERACTIFS POUR LA FORMATION DES GUIDES-INTERPRÈTES : UNE APPROCHE MODERNE (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article analyzes the importance and methods of creating interactive materials designed for the training of guide-interpreters. The use of digital technologies and interactive approaches significantly enhances linguistic and cultural competence, as well as the professional skills of future guides. Practical examples and concrete recommendations are proposed.